2016
DOI: 10.1016/j.maturitas.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the association of physical function and cognitive function with life satisfaction in older age: The Rancho Bernardo Study

Abstract: Objectives This study examines the cross-sectional associations of cognitive and physical function with life satisfaction in middle-class, community-dwelling adults aged 60 and older. Study Design Participants were 632 women and 410 men who had cognitive function tests (CFT) and physical function tasks (PFT) assessed at a clinic visit between 1988 and 1992, and who responded in 1992 to a mailed survey that included life satisfaction measures. Cognitive impairment was defined as ≤24 on MMSE, ≥132 on Trails B,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The former is older adults' basic ability that is essential to their daily living [23]. High physical function is associated with the amount of activity older people can engage in [24], which increases quality of life and life satisfaction [25][26][27]. High levels of physical functioning are a prerequisite for being active in old age; having this ability can enable older people to lead a fulfilling life by performing activities and gaining various experiences.…”
Section: Introductionmentioning
confidence: 99%
“…The former is older adults' basic ability that is essential to their daily living [23]. High physical function is associated with the amount of activity older people can engage in [24], which increases quality of life and life satisfaction [25][26][27]. High levels of physical functioning are a prerequisite for being active in old age; having this ability can enable older people to lead a fulfilling life by performing activities and gaining various experiences.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, late life health is assessed in terms of mobility limitations, limitations in activities of daily living (ADL), and psychological distress. These are all common areas of health problems in later life, and the burden of these afflictions in terms of societal costs is substantial [ 34 ]. Mobility limitations and ADL limitations are rare among people under the age of 40, but after the age of 40 the prevalence increase with age.…”
Section: Introductionmentioning
confidence: 99%
“…Life satisfaction is important to consider in older ages given the association with health and longevity. 5 Studies including older adults from the general population have shown that life satisfaction can increase with age, 5,6 and that poorer self-perceived health, 6 more physical impairments 7 and living alone/being unmarried are associated with lower levels of life satisfaction. 8 Contrary to common beliefs, life satisfaction does not seem to be associated with the level and severity of SCI, but instead with employment, marital status, perceived health, time since injury and secondary health conditions (SHCs), such as pain and bowel-related problems.…”
Section: Introductionmentioning
confidence: 99%